Participação em atividades domésticas de crianças e adolescentes com TDAH: implicações para a prática clínica - Camila Guimaraes Mendes (2017)
The household environment is a context of reference to children and may be informative about interventions with children and adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD). This disorder is treated with psychostimulants that seems efficient to decrease symptoms and improve academic performance. However, changes related to home context are not outcomes usually assessed and little is known about how families adapt to the challenges found in the home routine and strategies used. The aim of this dissertation was to investigate the household participation of children and adolescents with ADHD. To better answer investigative questions were raised, three studies were developed. The first study (presented as article 1) was an integrative review where was investigated the scientific knowledge about the household participation of children and adolescents with ADHD and discussed about potential implications for clinical practice. The second study (presented as article 2) aims to investigate associated factors to changes in performance of household tasks and assistance provided by caregivers of children with ADHD in treatment. Some factors were investigated for their importance in child development as parental styles and maternal psychiatric symptoms. The third (presented as article 3) investigated what strategies were used by the caregivers to support the participation of their children at home and classified the strategies as negative or positive. Also was investigated the associations between use of strategies and values and beliefs of parents related to domestic participation: importance attributed by caregivers and their satisfaction with child participation. Both studies (study 2 and 3) assessed children participation from the perspective of their caregivers using the Children Helping Out: Responsibilities, Expectations and Supports(CHORES). The article 2 count with information of 51 caregivers of children and adolescent with ADHD (6 to 14 years old) followed up for one year of pharmacological treatment while the article 3 included 100 caregivers of children with ADHD. In Article 1, five articles were included in a review of literature, showing the theme in question is still incipient. The lack of generalization of the results is an important limitation; however, this may be an unrealistic expectation in a clinical context, since ADHD is a heterogeneous health condition and considering all existing sociocultural diversity and families studied. More investigations are necessary to broad the knowledge about the profile of participation this population because other factors, are not explored, could influence the engagement of children in household tasks. In article 2, the changes of household participation of children with ADHD were significate showing increase of number of tasks performed as well as decrease in assistance provided by caregivers after sixteen months of pharmacological treatment. Maternal symptoms of ADHD and authoritarian parental style were predictive of changes in household task participation of children. For ADHD children in treatment, maternal psychological characteristics and styles and dimensions of parents had an impact in functional outcomes, emphasizing the importance of assess and approach family characteristics to improve the family environment and guide effective practices to this population. In article 3, was identified most families used any strategy at home to promote household task participation of children, although they use more negatives (i.e. punishment, treats) rather than positive strategies (i.e. praise, rewards). In context of ADHD, the kind of strategy used can have a significant impact in a familiar dynamic as well as to kid, explaining the relevance of this topic. There were no significant associations between the use of any strategy and the importance attributed by parents to children's household participation and satisfaction with participation. On the other hand, the level of satisfaction of parents was associated significantly with the use of positive strategies. Caregivers can base their choices of strategies on their satisfaction with performance of children. However, other factors not investigated in this study, as regarding to ADHD diagnosis as features of parents can be important to determinate the use or not of strategies at home. In turn, is important instruct parents to use appropriated strategies considering features of health condition of children and that also meet expectations of their caregivers regarding the household participation.